Professional Identity and Leadership Styles as Predictors of Job Performance of Teachers: An Explanatory Sequential Design - I. Ruego, Emee (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aimed to determine the influence of professional identity and leadership styles on the job performance of master teachers in Region XI. A mixed-methods approach, specifically a sequential explanatory design was utilized to understand the professional identity, leadership styles, and job performance of master teachers using the quantitative and qualitative data. The researcher made use of stratified sampling using 200 respondents for the quantitative design and 17 participants for the interview. The status of professional identity, leadership styles, and job performance was high among master teachers. In an individual capacity, professional identity and leadership styles significantly influence job performance of master teachers. The combined influence of professional identity and leadership styles as predictors of job performance was a good fit for the data in this study. The standpoint of the participants revealed their agreement to the relationship between professional identity, leadership styles, and job performance of master teachers. The joint display revealed the connecting-confirmation nature of data integration.